Consumer Rating Dynamics - André Stenzel; Christoph Wolf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We consider dynamic price-setting by firms in the presence of rating systems and asymmetric information about product quality. The current price determines the set of purchasing consumers and thereby affects future ratings and continuation profits. We outline the effects of prices on consumers' beliefs about quality as well as their review upon purchase. We provide a characterization of the firm's pricing decision in the presence of naive consumers who infer quality based on the observed aggregate rating, which reflects past consumers' gross utility, and price. We show that the firm charges a mark-up compared to the myopically optimal price: It restricts purchase to those consumers with a high degree of horizontal taste for the product which boosts reviews and hence future ratings and profits. Moreover, we show that if the firm takes the price's effect on reviews into account, the rating will not perfectly reveal the product's quality. If consumers hold a correct belief in the current period, future consumers will overestimate the product's quality.
Keywords: L00; D21; D83; 330